The Utilization of Digital Applications (Ngaji.AI) In Improving Students' Ability To Read and Memorize the Qur'an at MTs As'adiyah Gilireng - Firda Rezky Auliah; Raya Mangsi; Sumadin Sumadin (Universitas Islam Lamongan, 2026)
This study aims to examine the use of the Ngaji.AI application to improve students' Qur'anic reading and memorization abilities at MTs As'adiyah Gilireng. This research is motivated by challenges in Qur'anic learning, including limited learning time, low reading accuracy, and minimal use of digital media in rural madrasahs. The study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving teachers and students. The findings indicate that the use of the Ngaji.AI application has a positive impact on improving reading fluency, accuracy of makhraj and tajwid, and consistency of students' memorization. Artificial intelligence–based features such as automatic correction, real-time feedback, and audio repetition support independent learning while enhancing students' motivation and self-confidence. This study contributes to the growing body of research on AI-based Qur'anic learning.